SOX9 predicts progression toward cirrhosis in patients while its loss protects against liver fibrosis - Varinder S Athwal; James Pritchett; Jessica Llewellyn; Katherine Martin; Elizabeth Camacho; Sayyid MA Raza; Alexander Phythian‐Adams; Lindsay J Birchall; Aoibheann F Mullan; Kim Su; Laurence Pearmain; Grace Dolman; et al. (EMBO Molecular Medicine)
Abstract Fibrosis and organ failure is a common endpoint for many chronic liver diseases. Much is known about the upstream inflammatory mechanisms provoking fibrosis and downstream potential for tissue remodeling. However, less is known about the transcriptional regulation in vivo governing fibrotic matrix deposition by liver myofibroblasts. This gap in understanding has hampered molecular predictions of disease severity and clinical progression and restricted targets for antifibrotic drug development. In this study, we show the prevalence of SOX9 in biopsies from patients with chronic liver disease correlated with fibrosis severity and accurately predicted disease progression toward cirrhosis. Inactivation of Sox9 in mice protected against both parenchymal and biliary fibrosis, and improved liver function and ameliorated chronic inflammation. SOX9 was downstream of mechanosignaling factor, YAP1. These data demonstrate a role for SOX9 in liver fibrosis and open the way for the transcription factor and its dependent pathways as new diagnostic, prognostic, and therapeutic targets in patients with liver fibrosis.